Elevated Nutrient Supply Caused by the Approaching Kuroshio to the Southern Coast of Japan - Durán Gómez, Gloria Silvana; Nagai, Takeyoshi (Frontiers in Marine Science, 2022)
Although the Kuroshio Current has been well-known for being nutrient poor in its upper layers, it sustains a great biodiversity within its region, including the Kuroshio Extension. Previous studies reported that the Kuroshio carries a large amount of nutrients in its dark subsurface layers, yet, the mechanisms of how these nutrients are brought to sunlit layers remain unclear. In a previous observational study, it is shown that when the Kuroshio flows near the shelf break, very strong turbulence with dissipation rates of O (10 -7 W kg -1), caused by trapped near-inertial internal waves, leads to the generation of large diffusive nitrate fluxes of 1-10 mmol N m -2 day -1. Nevertheless, since these results were obtained from just one transect survey, questions remain, such as how long the enhanced turbulent diffusive nitrate flux extends downstream, and how the Kuroshio path modulations affect this nutrient injection. In this study, observed features were reproduced by using a high-resolution nested simulation coupled with a N2PZD2 ecosystem model. The results show that when the model Kuroshio flows closely to the coast, it hits a small bump in the upstream region of the Hyuganada Sea producing negative potential vorticity. At the same time, trapped near-inertial internal waves in a streak of lowered lowest internal wave frequencies are reproduced near the area with low PV values, generating strong vertical mixing similar to the observations. Since more nitrate is brought upward on the continental shelf when the Kuroshio approaches to the coast, the enhanced vertical mixing effectively diffuses up the nitrate from subsurface to surface layers at a rate of ~O(1 mmol N m -2 day -1) toward 50-100 km downstream along the Kuroshio. Further analyses on how the distance between the model Kuroshio and the southeastern coast of Kyushu affects the nutrient supply, suggest that when the Kuroshio flows closer to the coast, the internal wave kinetic energy, the nitrate concentration, its vertical gradients and vertical diffusive flux increase.